Beetroot Extracts as Haematopoietic Agents on Rats - Ni Putu Ermi Hikmawanti; Lusi Putri Dwita; Dinitia Az Zahra (Indonesian Journal of Pharmacy, 2021)
Introduction: Beetroot (Beta vulgaris L.) contains flavonoid compounds that play a role in the haematopoietic process. It is known that methanol extract of beetroot has benefits in the process of haematopoiesis in normal white rats. Aims: To evaluate the beetroots extracts as hematopoietic agents on male rats. Methods: Beetroots dried powder was divided into two parts. One part was macerated separately with dichloromethane and 70% ethanol, while the other part is added with citric acid and washed with water to remove alkaloids and then extracted with 70% ethanol. The study used 24 rats which were divided into four groups. Each group consisted of 6 rats, namely the normal group, dichloromethane extract group, ethanolic extract group, and free alkaloids-ethanolic extract group. Each extract was given at a dose of 200 mg.Kg-1 for 21 days. Analyzed blood parameters are erythrocytes, haemoglobin, MCV, MCH, MCHC, leukocytes, and platelets. The data obtained consisted of the number of cells analyzed using one-way ANOVA then obtained by the Tukey test. Results: This study showed a significant increase in the number of erythrocytes, haemoglobin, MCV, MCH, MCHC, leukocytes, and platelets in rats that were given each extract compared to the normal group (p <0.05). The ethanolic extract of beetroot can increase erythrocytes, haemoglobin, MCV, MCH, MCHC, leukocytes, and platelets by 41.49%, 24.95%, 14.92%, 33.54%, 27.19%, 59.40%, and 35.37%, respectively. Conclusions: The ethanolic extract of beetroot has the potential as a good natural haematopoietic agent.